2011
DOI: 10.1245/s10434-011-1824-y
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Outcomes and Survival in pT0 Tumors After Radical Cystectomy in Patients Without Neoadjuvant Chemotherapy: Results from a Large Multicentre Collaborative Study

Abstract: Despite acceptable oncological outcomes, patients with a pT0 tumor at the time of RC are still at risk of recurrence and progression and should not be considered to be entirely cured. In this population, stringent follow-up according to current recommendations should be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Clinical stage was also not found to be associated with OS in a multi-institutional series. 19 Our study has several limitations. It is a retrospective analysis, with accompanying inherent bias.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Clinical stage was also not found to be associated with OS in a multi-institutional series. 19 Our study has several limitations. It is a retrospective analysis, with accompanying inherent bias.…”
mentioning
confidence: 91%
“…18 Multiinstitutional reviews have also found that female gender, posterior tumour location and absence of lymph node dissection are associated with increased disease recurrence. 17,19 These patients may benefit from more stringent surveillance to allow identification of recurrence earlier with subsequent initiation of additional therapy.…”
mentioning
confidence: 99%
“…There is no definitive evidence regarding the recurrence rate after RC. In particular, the definition of local and distant recurrence is not standardized, the recurrence-free survival (RFS) is highly variable and the specific timing of recurrence is not well defined across the published series [ 2 5 ]. Several factors have been variously associated with recurrence after RC.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with neoadjuvant chemotherapy (NAC) in muscle invasive bladder cancer (MIBC) is associated with clinical benefit in urothelial carcinoma. Cisplatin-based NAC prior to extirpative surgery confers a 6-8% overall survival (OS) benefit compared to surgery alone [1]. Historically, the two most commonly utilized regimens include dose-dense methotrexate, vinblastine, doxorubicin, and cisplatin (dd-MVAC) or gemcitabine and cisplatin (GC), with pathological complete response (pT0) after NAC at the time of surgery being widely adopted as a surrogate end point for improved overall survival.…”
Section: Introductionmentioning
confidence: 99%